Neurogenesis in the rat neonate's hippocampus with maternal short‐term REM sleep deprivation restores by royal jelly treatment - Atena Khodaverdiloo; Mona Farhadi; Melikasadat Jameie; Seyed behnamedin Jameie; Vahid Pirhajati (Brain and Behavior, 2021)
Abstract Background Numerous studies have shown the effects of rapid eye movement sleep deprivation (REM‐SD) on behavior and brain structures. The impact of REM‐SD on learning and memory, thus neurogenesis, has been reported in previous studies. Royal jelly (RJ) is known as the wealthiest biological nutrient with various physiological properties. This study aimed to study the possible effect of RJ on neurogenesis of the rat hippocampus neonates following exposure of mother to REM‐SD during pregnancy. Methods Thirty neonate rats from 15 pregnant Wistar rats were used. To induce REM‐SD, the flowerpot method was used. The pregnant rats were divided into five groups (n = 3): group 1, no treatment; group 2, REM‐SD; groups 3, 4, and 5, REM‐SD +RJ. The former group received 72 h REM‐SD during pregnancy (days 7, 14, 21), and the latter group received REM‐SD + RJ (three trial groups). At week 4, the rat neonates of all groups were sacrificed (n = 6 each group). Their brains were fixed, removed, and prepared for Nissl and Hoechst 33342 staining. By using real time polymerase chain reaction methode the brain‐derived neurotrophic factor BDNF gene expression was studied (RT‐PCR), brain‐derived neurotrophic factor (BDNF) gene expression was studied. The results were analyzed statistically, and the Pv  < .05 was considered significant. Results The results showed a significant decrease in the number of neurons in the hippocampus of neonatal rats of REM‐SD mothers compared to the neonates of the mother with REM‐SD + RJ. REM‐SD also led to an increase in apoptosis reaching the neonates from the REM‐SD + RJ animals. High expression of BDNF was observed in the hippocampus of the neonates from REM‐SD + RJ treated mothers. Conclusion RJ acts as a neuroprotective agent that could compensate for the effects of REM‐SD on learning and memory via restoring neurogenesis.